Reactivity to myelin antigens in multiple sclerosis. Peripheral blood lymphocytes respond predominantly to myelin oligodendrocyte glycoprotein. - Kerlero de Rosbo, N (1993)
Although T cell responses to the quantitatively major myelin proteins, myelin basic protein (MBP) and proteolipid protein (PLP), are likely to be of importance in the course of multiple sclerosis (MS), cell-mediated autoimmune responses to other myelin antigens, in particular quantitatively minor myelin antigens, such as myelin-associated glycoprotein (MAG) and the central nervous system-specific myelin oligodendrocyte glycoprotein (MOG), could also play a prevalent role in disease initiation or progression. Highly purified myelin antigens were used in this study to assess cell-mediated immune response to MOG in MS patients, in the context of the reactivity to other myelin antigens, MBP, PLP, and MAG. The greatest incidence of proliferative response by MS peripheral blood lymphocytes was to MOG, as 12 of 24 patients tested reacted and, of these, 8 reacted to MOG exclusively. In contrast, only 1 control individual of 16 tested reacted positively to MOG. The incidence of responses to MBP, PLP, and MAG did not differ greatly between MS patients and control individuals. A predominant T cell reactivity to MOG in MS suggests an important role for cell-mediated immune response to this antigen in the pathogenesis of MS.